Educational Modernization and Innovation in Islamic Boarding Schools in Indonesia - Syafrizal Fuady; Husni Rahim; Mundzier Suparta; Ulfah Fajarini (International Journal of Islamic Educational Research, 2024)
Advances in digital technology in the current Industry 4.0 era have changed and influenced several aspects of human life. Suppose the Indonesian people do not want the identity and character of their community and their cultural riches to be lost at the hands of globalization. In that case, the community must have a robust defence mechanism. One way to build a defense system is through education. Technology and education are two things that cannot be separated. Pesantren is the oldest Islamic education and broadcasting institution in Indonesia. This research aims to examine and formulate the implications of the shift in orientation and value systems of Islamic boarding schools at the modern Islamic boarding school Nurussalam Sidogede (South Sumatra), the modern Islamic boarding school Darul A'mal (Metro Lampung), the Al-Hikmah Islamic boarding school (Bandar Lampung) and the modern Islamic boarding school Al -Muhajirin (Cikarang Bekasi) with an AGIL approach. This research uses a descriptive qualitative approach. The primary data used in this research is sourced from the author's interviews with the Islamic boarding school. The results show that there are several similarity and differences between the transformative Islamic boarding school and non-transformative Islamic boarding school groups in terms of variables or indicators, namely Adaptation (A), Integration (I), Goal (G), and Latent Patten (L).